Assessing the impact of storage conditions on RNA from human saliva and its application to the identification of mRNA biomarkers for asthma - Bhamidimarri, Poorna Manasa; Fuentes, David; Salameh, Laila; Mahboub, Bassam; Hamoudi, Rifat (Frontiers in Molecular Biosciences, 2024)
Human saliva was used to develop non-invasive liquid biopsy biomarkers to establishing saliva as an alternate to blood and plasma in translational research. The present study focused on understanding the impact of the sample storage conditions on the extraction of RNA from saliva and their RNA yield, to be applied in clinical diagnosis. In this study, genes related to asthma were used to test the method developed.Salivary RNA was extracted from three subjects using the Qiazol® based method and quantified by both spectrophotometric (NanoDrop) and fluorometric (Qubit®) methods. RNA integrity was measured using a bioanalyzer. Quantitative PCR was used to monitor the impact of storage conditions on the expression of housekeeping genes: GAPDH and β-actin, and the asthma related genes: POSTN and FBN2. In addition, an independent cohort of 38 asthmatics and 10 healthy controls were used to validate the expression of POSTN and FBN2 as mRNA salivary biomarkers. Approximately 2 µg of total RNA was obtained from the saliva stored at 40°C without any preservative for two weeks showing consistent gene expression with RNA stored at room temperature (RT) for 48 hours with RNAlater. Although saliva stored with RNAlater showed a substantial increase in the yield (110 to 234 ng/ µL), a similar Cq (15.6 ±1.4) for the 18s rRNA gene from saliva without preservative showed that the RNA was stable enough. Gene expression analysis from the degraded RNA can be performed by designing the assay using a low smaller fragment size spanning a single exon as seen heredescribed below in the case of the POSTN and FBN2 genes in the asthma cohort.This study showed that samples stored at room temperature and up until to a temperature of 40°C without any preservative for two weeks yielded relatively stable RNA. The methodology developed can be employed to transport samples from the point of collection to thea laboratory, underin non-stringent storage conditions, enabling the execution of gene expression studies in a cost effective and efficient manner.